2012
DOI: 10.1161/strokeaha.111.645499
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Artery Anatomy and Geometry as Risk Factors for Carotid Atherosclerotic Disease

Abstract: Background and Purpose-Traditional vascular risk factors do not completely explain the asymmetry, racial, and sex differences in carotid artery disease. Carotid anatomy and geometry may play a role in the pathogenesis of internal carotid artery (ICA) stenosis, but their effects are unknown. We hypothesized that carotid artery anatomy and geometry would be independently associated with ICA stenosis. Method-This is a retrospective study of patients with CT angiography at Monash Medical Centre, 2006 to 2007. Caro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
86
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(99 citation statements)
references
References 29 publications
9
86
2
2
Order By: Relevance
“…51 Ϯ 16°, P ϭ 0.14), which was consistent with the results of Bijari et al (3). In contrast, Phan et al (23) found a significant increase of the ICA angle in adults with mild and severe stenoses. This disagreement may be attributed to racial differences (people of Caucasian origin vs. Chinese) (28).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…51 Ϯ 16°, P ϭ 0.14), which was consistent with the results of Bijari et al (3). In contrast, Phan et al (23) found a significant increase of the ICA angle in adults with mild and severe stenoses. This disagreement may be attributed to racial differences (people of Caucasian origin vs. Chinese) (28).…”
Section: Discussionsupporting
confidence: 89%
“…Although a complete comparison showed significant difference of carotid artery bifurcations between control subjects and patients with carotid artery disease, the sample size (30 control subjects and 30 patients with carotid artery disease) in the retrospective study was relatively small compared with previous studies (3,23). This requires further analysis with larger sample size in a prospective study.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Vessel anatomy in turn influences the hemodynamic forces and as such the left carotid artery may be exposed to higher arterial pressures. 6,32 Flow models have shown that atherosclerotic plaques preferentially develop in areas with low wall shear stress, such as at bifurcations or inner curves. 33 Wall shear stress and stress inside the vessel wall may affect plaque formation and composition by causing alterations in wall structure and metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Furthermore, it is feasible that not only plaque severity but also plaque composition vary according to location. 8 Some plaque components, such as intraplaque hemorrhage (IPH), are presumed to enhance vulnerability of the plaque, whereas calcification may promote plaque stability.…”
mentioning
confidence: 99%